Assessment and management of pain during dressing change in patients with diabetic foot ulcers: a best practice implementation project. (October 2019) - Ren, Ying; Luo, Xiangrong; Xie, Cuihua; Zhang, Ping; Meng, Min; Song, Huijuan
ABSTRACT: Introduction: Pain caused by dressing change has adverse effects on patients with a diabetic foot ulcer, including sleep disturbances, immobility, depression and anxiety. It is crucial that healthcare professionals use a standardized tool to assess and document pain during dressing change and then use this information to inform strategies to alleviate the pain. Objectives: The aim of this project was to implement evidence-based practice in assessment and management of pain during dressing change among patients with diabetic foot ulcers in an endocrinology unit in a tertiary hospital. Methods: The JBI Practical Application of Clinical Evidence System (JBI PACES) and Getting Research into Practice (GRiP) audit and feedback tool were used for auditing clinical practice and translating evidence into practice. A baseline audit was performed to assess compliance with six criteria, followed by the implementation of evidence-based interventions to improve compliance. The follow-up audit using the same audit criteria was conducted to assess the effect of targeted strategies on compliance with best practice. Results: The baseline audit revealed that compliance with evidence-based practice was low, with only one of the six audit criteria achieving a compliance rate above 60%. After brainstorming and synthesizing the literature, the project team identified barriers and strategies for implementing best practice. The follow-up audit showed improvements in compliance across all six criteria, although there was only a small improvement in one of the criteria. The compliance rate of the other five criteria improved to greater than 67%. Conclusion: A best practice implementation project that involved standardizing pain assessment and management, and delivering education materials to nursing staff and patients was completed using JBI PACES and GRiP. The project improved nurses' compliance with best practice. Nurses attach importance to relieving patients' pain when they perform wound care, while patients with a diabetic foot ulcer gain access to high-quality wound care. Future studies will be conducted to address new barriers that emerged during the follow-up audit.